PENGARUH PERBANDINGAN TEPUNG BEKATUL BERAS MERAH DENGAN TERIGU TERHADAP KARAKTERISTIK BISKUIT - Dwi Cahyadi Putra, i Made; Wisaniyasa, Ni Wayan; Rai Widarta, I Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2015)
This study aims was to determine the effect of wheat flour and red rice bran flour ratio on the characteristic of biscuit and to find out the best ratio of wheat flour and red rice bran flour that produce biscuit with the best characteristic. The design of research was Completely Random Design (CRD). The treatment factor was ratio of wheat flour and red rice bran flour with 6 level: 100%:0%, 95%:5%, 90%:10%, 85%:15%, 80%:20% and 75%:25%. Each treatment was repeated three times in order to obtain 18 experimental units. The results showed that the ratio of wheat and red rice bran flour in the production of biscuit has effect on the water content, ash content, protein content, fat content, carbohydrate content, crude fiber, IC50 value, color, texture, flavor, taste, and overall acceptability.  Ratio of 90% wheat flour and 10% red rice bran flour produced biscuit with the best characteristic with characteristic 3.14% water content, 1.22% ash content, 24.26% fat content, 11.09% protein content, 60.29% carbohydrate, 3.50 % grunge fiber content, 2.22% IC50, yellowish brown, rather liked color, rather liked texture, rather liked flavor, rather liked taste and rather liked overall acceptability.
Keywords: red rice bran flour, wheat, biscuit, ratio.